Impaired coagulation parameters in early RA are restored by effective antirheumatic therapy: a prospective pilot study - Ronald F van Vollenhoven; Merete Lund Hetland; Till Uhlig; Espen A Haavardsholm; Dan Nordström; Aleksandra Antovic; Mikkel Østergaard; Michael T Nurmohamed; Bjorn Gudbjornsson; Gerður Gröndal; Kim Hørslev-Petersen; Anna Rudin; et al. (RMD Open)
Objectives To assess the effect of treatment on haemostatic parameters in patients with early rheumatoid arthritis (RA).Methods Patients with newly diagnosed RA started methotrexate and were randomised to additional conventional treatment, certolizumab pegol, abatacept or tocilizumab. Several biomarkers for haemostasis were analysed including parameters of the two global haemostatic assays—overall haemostatic potential (OHP) and endogenous thrombin potential (ETP), as well as single haemostatic factors—fibrinogen, prothrombin fragment 1+2 (F1+2), D-dimer, thrombin activatable fibrinolysis inhibitor (TAFI) and clot lysis time (CLT) in 24 patients at baseline, 12 and 24 weeks after the start of the treatment.Results At baseline, patients had elevated levels of the following biomarkers compared with reference values: fibrinogen, F1+2, D-dimer and parameters of the two global haemostatic assays, that is, ETP and OHP. After 24 weeks we observed a significant reduction in F1+2 (p<0.01), fibrinogen (p<0.01), D-dimer (p<0.01), OHP (p<0.01), ETP (p<0.01), CLT (p<0.01), TAFI (p<0.01) and an increase of OFP (p<0.01). Tocilizumab treatment resulted in the most significant reduction of global haemostatic assays after 24 weeks, that is, a reduction of OHP 73% (p<0.01) compared with certolizumab pegol arm 32% (p<0.01), abatacept arm 24% (p=0.25) or conventional treatment arm 7% (p=0.66).Conclusion Newly diagnosed RA patients have enhanced coagulation activation and impaired fibrinolysis as demonstrated by our results. Effective antirheumatic treatments during the first 24 weeks after diagnosis improved this haemostatic imbalance, with prominent effects of biological drugs and especially tocilizumab, compared with conventional treatment.